Dampak Disfungsi Seksual terhadap Frekuensi Hubungan Seksual Pada Wanita Perimenopause di Desa Guradog Curugbitung Lebak Banten - Siti Nurhidayati; Maryati Sutarno (Universitas Malahayati Lampung, 2024)
ABSTRACT Perimenopause is a transitional period of a woman's cycle that starts from the end of the reproductive stage and ends five years before menopause, around the age of 45-59 years. Perimenopause often experiences sexual dysfunction. Changes in sexual function is one of the causes of a decrease in the frequency of sexual intercourse. The results of a preliminary study in Guradog Curugbitung Lebak Village on 10 perimenopausal women found that 70% experienced sexual dysfunction with 90% having sexual intercourse once a month and 10% of people who had not had sexual intercourse. Knowing the impact of sexual dysfunction on the frequency of sexual intercourse in perimenopausal women in Guradog Curugbitung Village, Lebak, Banten in 2023. This research is a quantitative analytic study with a cross sectional design. The sample in this study were perimenopausal women who still have husbands totaling 75 respondents using purposive sampling technique. The research instrument used a questionnaire. Data is primary data analyzed using square test. The results of univariate analysis showed that most of the perimenopausal women had sexual dysfunction 56.0% and frequency of infrequent sexual intercourse 54.0%. The results of the bivariate analysis showed the impact of sexual dysfunction on the frequency of sexual intercourse in perimenopausal women with a p value = 0.000. Sexual dysfunction has an impact on the frequency of sexual intercourse in perimenopausal women. Perimenopausal women are expected to increase their knowledge, especially with regard to efforts to prevent sexual dysfunction, such as warming up beforehand, or consulting with health workers because it has an impact on the frequency of sexual intercourse, causing disharmony in the household. Keywords: Sexual Dysfunction, Frequency of Sexual Intercourse, Perimenopause ABSTRAK Perimenopause adalah masa transisi siklus wanita yang berawal dari akhir tahap reproduksi dan berakhir lima tahun sebelum menopause, sekitar umur 45-59 tahun. Perimenopause sering mengalami gangguan fungsi seksual. Perubahan fungsi seksual menjadi salah satu penyebab penurunan frekuensi hubungan seksual. Hasil studi pendahuluan di Desa Guradog Curugbitung Lebak terhadap 10 wanita perimenopause ditemukan 70% mengalami disfungsi seksual dengan 90% melakukan hubungan seksual 1 bulan sekali dan 10% orang sudah tidak melakukan hubungan seksual. Mengetahui dampak disfungsi seksual terhadap frekuensi hubungan seksual pada wanita perimenopause di Desa Guradog Curugbitung Lebak Banten tahun 2023. Penelitian ini merupakan penelitian analitik kuantitatif dengan rancangan cross sectional. Sampel dalam penelitian ini adalah wanita perimenopause masih mempunyai suami berjumlah 75 responden dengan teknik purposive sampling. Instrumen penelitian menggunakan kuesioner. Data merupakan data primer dianalisis menggunakan uji uji square. Hasil analisis univariat diketahui sebagian besar wanita perimenopose dengan disfungsi seksual 56,0% dan frekuensi hubungan seksual jarang 54,0%. Hasil analisis bivariat terdapat dampak disfungsi seksual terhadap frekuensi hubungan seksual pada wanita perimenopause dengan nilai p value = 0,000. Disfungsi seksual berdampak terhadap frekuensi hubungan seksual pada wanita perimenopause. Wanita perimenopause diharapkan dapat meningkatkan pengetahuannya khususnya yang berkaitan dengan upaya dalam pencegahan terjadinya disfungsi seksual seperti melakukan pemanasan terlebih dahulu, atau berkonsultasi dengan tenaga kesehatan karena berdampak pada frekuensi hubungan seksual sehingga menimbulkan terjadinya ketidak harmonisan dalam rumah tangga. Kata Kunci: Disfungsi Seksual, Frekuensi Hubungan Seksual, Perimenopause